Ongoing HIV-1 transmission among men who have sex with men in Amsterdam: a 25-year prospective cohort study - Jansen, I; Geskus, R; Davidovich, U; Jurriaans, S; Coutinho, R; Prins, R; Stolte, M (Lippincott, Williams and Wilkins, 2011)
Background: To examine the suggested resurgence of the HIV epidemic among men who have sex with men (MSM), we studied trends in HIV-1 incidence rates, sexual risk behaviour, risk factors for HIV-1 seroconversion, and source of HIV-1 infection among MSM in the Amsterdam Cohort Studies from 1984 to 2009. Methods: Trends in HIV-1 incidence and risk factors for HIV-1 infection were studied using Poisson regression. Trends in sexual risk behaviour were evaluated using logistic regression, correcting for intra-individual correlation via generalized estimating equations. Trends in the source of HIV-1 infection were modelled via logistic regression. Results: Of 1642 HIV-1-negative individuals, 217 seroconverted during follow-up. HIV-1 incidence rates strongly decreased from 8.6/100 person-years in 1985 to 1.3/100 person-years in 1992; remained relatively stable around 1.0/100 person-years between 1992 and 1996, and slowly increased to 2.0/100 person-years in 2009 (P = 0.14; linear trend 1996–2009). Reports of unprotected anal intercourse (UAI) increased significantly from 1996 onwards. HIV-1 seroconversion was associated with receptive UAI with casual partners, more than five sexual partners, a history of gonorrhoea (all in the preceding 6 months), and a lower educational level. Currently, MSM are more likely to have contracted HIV-1 from casual partners than from steady partners, but trends of recent years suggest that steady partners became a growing source with increasing age. Conclusions: Following increases in sexual risk behaviour from 1996 onwards, HIV-1 continues to spread among MSM. Targeted prevention messages should continue to focus on sexual behaviour with casual partners, but also on sexual behaviour within steady relationships.